Autonomic nervous system functions in children with nocturnal enuresis - Yakinci, C; Mungen, B; Durmaz, Y; Balbay, D; Karabiber, H (Elsevier Science Bv, 1997)
Nocturnal enuresis is involuntary urination during night sleep, The pathogenesis of nocturnal enuresis is controversial. Developmental delay, genetic factors, stress and psychological factors, and sleep abnormalities are considered to be the etiologic factors. Various urodynamic studies showed bladder hyperactivity in enuretic children. Since the cause of vesical hyperactivity is not clear, we investigated the possible role of autonomic nervous system dysfunction in these children. The study groups consisted of 41 enuretic (25 boys and 16 girls) and 30 healthy children (18 boys and 12 girls). Four non-invasive autonomic nervous system function tests (orthostatic test, Valsalva ratio, 30:15 ratio, heart rate responses to deep breathing) were carried out in both groups. The differences between the enuretic and control groups were statistically significant in the Valsalva and 30:15 ratios (P < 0.0005 and P < 0.005, respectively). The results of these two tests demonstrated parasympathetic nervous system hyperactivity. No abnormality of the sympathetic nervous system was found. We suggest that the parasympathetic nervous system hyperactivity shown in our study may be a cause of vesical hyperactivity in enuretic children. (C) 1997 Elsevier Science B.V.
5th AOCCN Conference -- OCT 09-11, 1996 -- ISTANBUL, TURKEY
Keywords: enuresis; autonomic nervous system; child